KONSEP KEADILAN SOSIAL DALAM KITAB SUCI: STUDI KOMPARATIF DALAM AGAMA ISLAM DAN KONGHUCU - Ashri, Zainul (UIN Sumatera Utara Medan, 2023)
Justice is something central, and to which society aspires greatly. Justice cannot be separated from the prevailing legal order. Society as implementers and observers of the legal order has benchmarks oriented to ethical values and morality that cause the legal order to be obeyed and even abandoned. In addition, social society is also governed by religious norms which are also the main reference in determining the good and bad of something. Each of the beliefs will teach its adherents to uphold the value of justice in life, both social life and state life. This paper tries to compare the concept of justice from Islam and Confucianism, therefore, this paper focuses on knowing what are the concepts of justice offered by Islam and Confucianism. With comparative literature study and analysis, as far as research on the concept of justice from Islam and Confucianism found several findings, including: Islam teaches the concepts of justice: trust, honesty and equality. Confucianism teaches the concepts: morality, honesty, love and public interest. At first glance, the concepts of justice offered by Islam and Confucianism almost all have something in common. But in addition, the striking difference from the concept offered by the two religions is related to the concept of amanah from Islam. This shows that Islam teaches everything based on science. Amanah in terms of language does mean trustworthy, but more deeply mandate requires a leader to have qualified knowledge. So that with his knowledge will give birth to love, honesty and equality.